Acceptance of technological changes and job performance among administrative support personnel in the government offices in Maran, Pahang Darul Makmur / Hazlin Hasan and Feridah Hj Mohd Nadzar - Hasan, Hazlin; Mohd Nadzar, Feridah (Universiti Teknologi MARA Cawangan Pahang, 2010)
The study was conducted to develop an understanding of the role of acceptance of technological changes as a pre-diction of the administrative support personnel job performance in the government offices. The rapid changes in technology have led to many challenges and changes that affect all levels of management in an organization. Em-ployees might experience difficulties for not being able to cope with the changes and it is feared that such behavior can influence their job performance. Using a survey method, data were gathered from 101 administrative support personnel employed in the government offices in the district of Maran, Pahang Darul Makmur. The Davis, 1989 Technology Acceptance Model was used to determine the relationship between Perceived Ease of Use and Per-ceived Usefulness of technology and job performance. Result shows that the issues in acceptance of technological changes are positively and significantly correlated with job performance. The study concludes that technological issues investigated were very important in ensuring higher acceptance of technological changes, thus improve the performance of the employees in the government offices.